Comparison of Outcome of Appendectomy: Laparoscopic versus Open Surgery in Combined Military Hospital, Savar - Iqbal, Mohammad Faruq; Chowdhury, Arif Imtiyaz; Rushdi Aziz, Sharkar (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Open appendectomy and laparoscopic appendectomy are two modalities in the treatment of appendicitis. Superiority of one over another is not clear. Objectives: To compare per-operative and post operative outcomes between open and laparoscopic appendectomy. Material and Methods: Prospective comparative study was conducted on patients with acute appendicitis who underwent open appendectomy (OA) (n=43) or laparoscopic appendectomy (LA) (n=59) from October 2018 to October 2019 in Combined Military Hospital (CMH), Savar. The two groups were compared in respect to patients' characteristics, duration of operation, operative findings, post operative pain, return of peristalsis, resume of oral feeding, post operative complications, return to activities and cosmesis. Statistical analysis was performed using SPSS 25.0. Continuous and categorical variables were analyzed using independent sample t test and chi-square test respectively and p <0.05 was considered statistically significant. Results: There was no statistical difference regarding patient characteristics between the two groups except total leukocyte count (TLC) and neutrophil count, both were higher in OA group (p<0.001). LA group was associated with less post operative pain (p<0.001), early resume of oral feed (OA-34.74±8.34 minutes vs LA-24.51±6.13 minutes; p<0.01), early return to light work (OA-4.26±1.3 days vs LA-2.53±0.7 days; p<0.001), heavy work (OA-66.93+19.38 days vs LA-37.36+10.02 days; p<0.001) and better cosmesis (highly satisfied in LA group 96.6% vs 30.2% in OA group). No significant difference was seen in duration of operation (50±13.72 and 53.31±7.69 minutes in OA and LA groups respectively; p>0.05). There was no significant difference in post operative complications (p>0.05). Conclusion: Laparoscopic appendectomy was found clearly superior to open appendectomy in terms of less post operative pain, early resume of oral feed, early return to light and heavy works and better cosmetic result. Both procedures are comparable in terms of duration of operation and post operative complications. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 51-54